Analysis of Good Corporate Governance, Free Cash Flow, Leverage towards Earning Management, and Shareholder Wealth in Service Sector Companies Listed on the Indonesia Stock Exchange - Yannizar Yannizar; Wazirman Wazirman; Gina Septiana (Budapest International Research and Critics University, 2020)
The phenomenon of the